A Study on Recidivism and its Influence on Family and Society: Exploring the Impact of Family Dynamics on Recidivism Rate in Kerala (Journal of Advances and Scholarly Researches in Allied Education, 2020)
This study's objective was to investigate the role that family dynamics have in the recidivismrate of criminals in Kerala. According to the findings of the study, the emotional and instrumentalsupport that is necessary for ex-offenders' successful reintegration into society is sometimes replacedby discrimination. Furthermore, the study found that when ex-offenders are confronted with the inabilityto provide for their children, marital crisis, and other challenges that are unique to ex-convicts,depression sets in and drives their disposition toward criminal activities. Therefore, variables that occurinside families also contribute to Kerala's exceptionally high prevalence of recidivism. As aconsequence of this, it has been suggested that the criminal justice system implement mechanisms tofacilitate positive contacts between convicted individuals and their families. The goals of thesemechanisms would be to strengthen family ties and to make it easier for families to receive assistancein a more timely manner.